DETERMINING COST CONTROL TECHNIQUE AND OVERCOMING CHALLENGES IN DAILY OPERATIONS: PERSPECTIVES FROM THE FOODSERVICE MANAGERS - Noor Azimin Zainol; Eshaby Mustafa; Roshita Abdul Razak; Rozila Ahmad, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
As more new players enter the market, the Malaysian food and beverage industry is anticipated to have a bright future. Hence, it is becoming increasingly important to comprehend how food and beverage establishments make profits through cost control measures, an important aspect that is frequently overlooked academically. Limited studies have been conducted towards understanding cost control matters, especially in the Malaysian setting. This paper highlights the critical cost control techniques and ways to overcome issues in food service operations. An exploratory approach via qualitative study is deemed feasible to investigate cost control measures being practiced in their daily operations. Cost control techniques applied in the Malaysian food and beverage industry needs to be determined. Further, how managers overcome challenges in manning their food and beverage outlets needs exploration. Therefore, in answering the questions, semi-structured interview protocols were conducted on 25 foodservice outlet managers around the northern part of Malaysia. The findings suggested that most of the managers interviewed understand cost control techniques needed to operate outlets based on their routine experience of running their operations. In terms of overcoming the challenges, these managers depicted several solutions which reflected the survival of their business. Thus, some recommendations can be suggested to improve their daily operations to cultivate the correct application of cost control measures in food and beverage outlet operations.